Knowledge, attitude, and behavior about sexual and reproductive health among adolescent students in Denpasar, Bali, Indonesia - Putu Erma Pradnyani; I Gusti Ngurah Edi Putra; Ni Luh Eka Purni Astiti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Adolescent sexual and reproductive health (SRH) problems remain an important public health issue in many developing countries, such as Indonesia. Therefore, assessing SRH knowledge, attitude, and behavior among adolescents are worth considering for public health intervention purpose in order to reduce their vulnerability to SRH problems.Aims: This study aimed to assess SRH knowledge, attitude, and behavior among adolescent students in Denpasar, Bali, Indonesia.Methods: This was a cross-sectional school-based study conducted in Denpasar, Bali, Indonesia from July to September 2016. This study applied multi-stage random sampling to recruit 1,200 students out of 24 junior, senior, and vocational high schools. Variables in this study consisted of socio-demographic characteristics, knowledge, attitude, and behavior related to SRH. Data were analyzed using descriptive analysis and cross-tabulation to identify proportion differences.Results: Regarding knowledge on SRH, students had less knowledge on a reproductive process (10.1%) and reproductive risk (11.4%), but half of them knew about the sexually transmitted infections (STIs) and HIV&AIDS (55.6%) and almost all had sufficient knowledge on puberty (90.7%). Meanwhile, few students argued that several sexual behaviors can be performed before getting married, such as kissing and hugging (48.9%), petting and oral sex (18.7%) and sexual intercourse (vaginal sex) (13.8%). Out of 1,200 adolescent students, 880 (73.3%) reported for have ever been in dating with someone. Among adolescent dating, few students reported for an experience of petting (14.3%), oral sex (9.8%), vaginal sex (6.5%), and anal sex (2.6%).Conclusion: Adolescent students in Denpasar, Bali, had a low level of sufficient knowledge in some SRH aspects, a few students reported for permissive attitude and performed premarital sexual behaviors. Therefore, providing comprehensive sexuality education (CSE) is worth considering to improve knowledge and appropriate skills in order to prevent risky sexual behavior among adolescents. Keywords: Sexual and reproductive health (SRH), Adolescents, Students, Knowledge, Attitude, Sexual behavior Received: 26 October 2018, Reviewed: 08 January 2019, Received: in revised form 25 February 2019, Accepted: 28 February 2019 DOI: 10.35898/ghmj-31554